Indentation densification of fused silica assessed by raman spectroscopy and constitutive finite element analysis - Bruns, Sebastian; Uesbeck, Tobias; Fuhrmann, Sindy; Aymerich, Mariona Tarrago; Wondraczek, Lothar; de Ligny, Dominique; Durst, Karsten (Journal of the American Ceramic Society, 2020)
Inelastic deformation of anomalous glasses manifests in shear flow and densification of the glass network; the deformation behavior during indentation testing is linked strongly to both processes. In this paper, the indentation densification field of fused silica is investigated using depth-resolved Raman spectroscopy and finite element simulations. Through affecting the size of the indent, the normal load and the Raman laser spot size determine the spatial sampling resolution, leading to a certain degree of structural averaging. For appropriate combinations of normal load (indent size) and laser spot diameter, a maximum densification of 18.4% was found at the indent center. The indentation behavior was modeled by extended Drucker-Prager-Cap (DPC) plasticity, assuming a sigmoidal hardening behavior of fused silica with a densification saturation of 21%. This procedure significantly improved the reproduction of the experimental densification field, yielding a maximum densification of 18.2% directly below the indenter tip. The degree of densification was found to be strongly linked to the hydrostatic pressure limit below the indenter in accordance to Johnson's expanding cavity model (J. Mech. Phys. Solids, 18 (1970) 115). Based on the good overlap between FEA and Raman, an alternative way to extract the empirical correlation factor m, which scales structural densification to Raman spectroscopic observations, is obtained. This approach does not require the use of intensive hydrostatic compaction experiments.
CRIS-Team WoS Importer:2020-02-07

Influence of Al2O3 Addition on Structure and Mechanical Properties of Borosilicate Glasses - Bruns, Sebastian; Uesbeck, Tobias; Weil, Dominik; Möncke, Doris; van Wüllen, Leo; Durst, Karsten; de Ligny, Dominique (Frontiers in Materials, 2020)
Alkali-borosilicate glasses are one of the most used types of glasses with a high technological importance. In order to optimize glasses for diverse applications, an understanding of the correlation between microscopic structure and macroscopic properties is of central interest in materials science. It has been found that the crack initiation in borosilicate glasses can be influenced by changes in network interconnectivity. In the NBS2 borosilicate glass system (74.0SiO2-20.7B2O3-4.3Na2O-1.0Al2O3 in mol%) two subnetworks are present, i.e., a silicate and a borate network. Increasing cooling rates during processing were found to improve glasses crack resistance. Simultaneously, an increase in the network interconnectivity accompanied by an increasing capacity for densification were noticed. Their individual contribution to the mechanic response, however, remained unclear. In the present study the borosilicate glasses were systematically modified by addition of up to 4.0 mol% Al2O3. Changes in the network connectivity as well as the short- and medium-range order were characterized using Raman and NMR spectroscopy. Both the Raman and the 11B NMR results show that four-fold-coordinated boron is converted into three-fold-coordination as the Al2O3 content increases. Additionally, 27Al NMR experiments show that aluminum is dominantly present in four-fold coordination. Aluminum-tetrahedra are thus charge balanced by sodium ions and incorporated into the silicate network. Finally, nanoindentation testing was employed to link the inherent glass structure and its network configuration to the mechanical glass response. It was found that the glass softens with increasing Al2O3 content, which enhances the crack resistance of the borosilicate glass.
CRIS-Team Scopus Importer:2020-08-21
Keywords: Brillouin; glass structure; indentation; mechanical testing; NMR; Raman; spectroscopy

Influence of Vanadium on Optical and Mechanical Properties of Aluminosilicate Glasses - Cicconi, Maria Rita; Lu, Zhuorui; Uesbeck, Tobias; Van Wuellen, Leo; Brauer, Delia S.; de Ligny, Dominique (Frontiers in Materials, 2020)
V2O5 was introduced up to 9 wt.% in a peralkaline alkaline earth aluminosilicate glass and up to 4.8 wt.% in two sodo aluminosilicate glasses, respectively, a peralkaline and a peraluminous one. This introduction had a strong effect on thermal properties, and in particular, on glass transition and crystallization temperatures of the peraluminous glass, which dropped by 89 K, while a moderate drop of similar to 20 K was observed for the two other glasses. Still, the glass stability and the glass-forming ability stayed almost unmodified. The elastic properties measured by Brillouin spectroscopy show a decrease with added Vanadium for the depolymerized alkali earth aluminosilicate and the peraluminous sodo aluminosilicate. In contrast, the elastic properties remained unchanged for the peralkaline composition. Using optical absorption, the proportion of V5+, which is largely dominant, was found to follow the trend predicted using optical basicity considerations. A large photoluminescence emission, centered at similar to 560 nm, was found for all glasses, upon excitation in the UV edge at both similar to 280 and similar to 350 nm. The emission band positions were relatively insensitive to the glass composition, whereas their intensities show variations of one order of magnitude between the sodium peralkaline composition and the calcium depolymerized glass. A too-high concentration of V(2)O(5)shows a quenching effect on the emission. Polarized and cross-polarized Raman spectroscopy allowed us to identify the different environments around the V5+O4 tetrahedra. The highly polarizable V5+O4 tetrahedra associated with two non-bridging oxygens, vibrating at 860 cm(-1), is proposed to be responsible for the more efficient charge transfer. At the opposite end, the formation of VO4-AlO4 units is proposed to quench luminescence properties. Furthermore, we observed that, upon thermal treatment, the optical properties of the glasses are significantly modified without observable structural modifications or evolution of the elastic properties.
CRIS-Team WoS Importer:2020-07-31